Physical activity participation among families of children with visual impairments and blindness. Issue 3 (30th January 2019) - Columna, Luis; Dillon, Suzanna Rocco; Dolphin, Michelle; Streete, Denzil A.; Hodge, Samuel R.; Myers, Beth; Norris, Michael L.; McCabe, Lindsay; Barreira, Tiago V.; Heffernan, Kevin S.
Abstract: Purpose: Physical activity (PA) provides multiple benefits to children with visual impairments (VI) and their families. However, the empirical literature base is underdeveloped on how family PA experiences impact participation for children with VI. The purpose of this study was two-fold; that is: (a) to explore why families with children with VI seek out and participate in PA, and (b) to describe the strategies and supports needed by families of children with VI to improve PA participation. Method: The research method was descriptive–qualitative positioned in the theoretical framework of the theory of planned behavior. Participants were parents of children with VI ( n  = 10) who took part in one-on-one semi-structured telephone interviews. Interview recordings were transcribed and analyzed using a thematic line-by-line analysis. Results: Three salient, recurrent, and interrelated themes emerged from the data analyses. These themes were: (a) committed, (b) challenged, and (c) access. Conclusions: Findings revealed that parents valued PA, but they lacked the skills to teach and advocate for their children regarding PA. As a consequence, parents voiced the need for a support system that would allow their families to be more physically active. Implications for Rehabilitation: Results of this study demonstrated that parents valued physical activity, but they lacked the skills necessary to confidently engage their children in physical activity. Physical activity interventions are needed to enhance the quality of life of children with visual impairments and their families. Physical activity programs and interventions are most likely to enhance intentions to engage in physical activity among children with visual impairments and their parents. Results demonstrated that parents of children with visual impairments were interested to work side-by-side with physical activity professionals to enhance recreational physical activity opportunities available to their children.